The taxman in post-apartheid South Africa : taxpayers’ perceptions for the period 1994 to 2007 - Molebalwa, Keamogetswe (University of Pretoria, 2023)
Mini Dissertation (MPhil (International Taxation))--University of Pretoria, 2022.